En första kriminologisk inblick i lagen (2007:1150) om tillsyn över hundar och katter - Sirkku Sarenbo; Helena Striwing (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract We present a first criminological insight into the Act (2007:1150) on the supervision of dogs and cats in terms of reporting and prosecution statistics, against the background of statistics on authority decisions based on this law, appeals of authority decisions and statistics from Folksam and the central dog register of the Swedish Board of  Agriculture. The number of prosecutions under the Supervision Act in the district courts is 30-46 prosecutions per year between 2004 and 2021. Women account for 65% of dog ownership and for 42% of offenses against the Supervision Act. The proportion of reports received that led to a decision by the County Administrative Boards varied from zero to approx. 30% in 2020 and 2021. Of the 13 persons who died due to dog-related injuries 1998-2021 seven were women, in the age groups 45 and older, while of 6 180 patients who required inpatient care for dog-related injuries 2001-2021 made up 648 children of 0-4 years old. Introduction of the current Supervision Act in 2008 resulted in an increased load on administrative courts, while  criminal cases in the district courts have been at about the same level as before. Transfer of responsibility for the Supervision Act from the Swedish Police Authority to the County Administrative Boards in 2018 increased the workload of the administrative courts even more. The criminal cases that are settled in the district courts no longer deal with first-time incidents where bite-prone dogs have caused property or personal damage or considerable inconvenience, but recurrences where society already had intervened through authority decisions, reflecting ineffectiveness of authority decisions based on the law. Not to criminalize Section 1 of the Supervision Act and transfer of responsibility for the law from the Swedish Police Authority to the County Admi- ESSAY nistrative boards have reduced the burden on the Police Authority and the district courts at the expense of an increased burden on the County Administrative boards and the administrative courts. The question is what, from a socio-economic perspective, is the best solution to  approach the problem of dangerous dogs.